The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1063/1.371403
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of Pb(Nb,Ti)O3 thin films by metalorganic chemical vapor deposition

Abstract: Lead niobium titanate, Pb(Nb,Ti)O3, thin films were prepared on various substrates by metalorganic chemical vapor deposition from the Pb(C11H19O2)2–Nb(O⋅C2H5)5–Ti(O⋅i-C3H7)4–O2 system. Polycrystalline films with (111) orientation and epitaxially grown films with c-axis orientation were deposited on the (111)Pt/Ti/SiO2(100)Si and PbTiO3/(111)Pt/Ti/SiO2/(100)Si substrates, and (100)SrRuO3//(100)LaAlO3 substrate, respectively, at 620 °C. Nb content in the film can be controlled only by changing the input gas flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…The apparatus and the procedures for film deposition have been described in a previous paper [8]. We used a tubular, horizontal, cold-wall reactor.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The apparatus and the procedures for film deposition have been described in a previous paper [8]. We used a tubular, horizontal, cold-wall reactor.…”
Section: Methodsmentioning
confidence: 99%
“…The investigation into the PZT-family thin films has been extended to a wide composition range, such as Pb(Ti,Nb)-O 3 , [8] (Pb,La)(Ti,Zr)O 3 , [13] (Ba,Sr)TiO 3 , [14] etc. In the first two systems, formation of the perovskite-type, body-centered tetragonal phase is a key consideration in obtaining the desired ferroelectric properties, such as high remnant polarization, low coercive field, high resistance, etc.…”
Section: Origin Of Co-existence Of Several Phases In the Thin Filmmentioning
confidence: 99%
See 1 more Smart Citation
“…Our theoretical investigation of SCLC began with a study of the well-known phenomenon of polarization offsets in compositionally graded ferroelectric films (Bao et al 2000a(Bao et al , 2000b(Bao et al , 2000c(Bao et al , 2001a(Bao et al , 2001bBouregba et al, 2003;Brazier et al, 1998;Chen et al, 1999;Mantese et al, 1997;Matsuzaki & Funakubo, 1999;Schubring et al, 1992). Ferroelectric materials are materials that generally exhibit nonlinear, hysteretic D-E or P-E relations, where D is the electric displacement, P is the polarization and E is the electric field.…”
Section: Polarization Offsets In Graded Ferroelectrics and The Need Fmentioning
confidence: 99%
“…Many authors have reported shifts of hysteresis loops, so called polarization offsets (P off ), observed on compositionally graded ferroelectric devices (GFD's) prepared with different material systems [1][2][3][4][5][6][7][8][9][10][11]. Offsets were systematically obtained while the devices were "pumped" by an oscillatory field during SawyerTower (S-T) hysteresis measurements [12] and their direction was directly 68 R. Bouregba et al…”
Section: Introductionmentioning
confidence: 99%